Bilateral morgagni hernia in a case of Weill-Marchesani syndrome-a rare association - Chetambath, Ravindran; Parengal, Jabeed; Aslam, Mohammed; Shivashankaran, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Morgagni hernia constitutes only about 2% of all diaphragmatic hernias and bilateral Morgagni hernia is extremely rare. Here we present a 75 year old female patient with morphometric features of Weill-Marchesani syndrome who has bilateral Morgagni hernia. This association is reported for the first time in literature.